Phosphate recovery as vivianite using a flow-electrode capacitive desalination (FCDI) and fluidized bed crystallization (FBC) coupled system. (15th April 2021) - Zhang, Changyong; Cheng, Xiang; Wang, Min; Ma, Jinxing; Collins, Richard; Kinsela, Andrew; Zhang, Ying; Waite, T. David
Highlights: An integrated FCDI/FBC system was fabricated for recovery of P as vivianite FCDI realized 63% P removal with pre-concentration in flow-electrode chamber FBC resulted in immobilization of 80% P as crystalline vivianite Readily separable high-purity vivianite crystals obtained after 372-hr operation Abstract: It is critical to both effectively remove and recover phosphate (P) from wastewater given the wide-ranging environmental (i.e., preventing eutrophication and restoring water quality) and economic (i.e., overcoming P resource scarcity) benefits. More recently, considerable academic effort has been devoted towards harvesting P as vivianite, which can be used as a potential slow-release fertilizer and possible reagent for the manufacture of lithium iron phosphate (LiFePO4 ), the precursor in fabricating Li-ion secondary batteries. In this study, we propose an innovative P recovery process, in which P is first preconcentrated via a flow-electrode capacitive deionization (FCDI) device followed by immobilization as vivianite crystals in a fluidized bed crystallization (FBC) column. The effects of different operational parameters on FCDI P preconcentration performance and energy consumption are investigated. Results show that 63% of P can be removed and concentrated in the flow-electrode chamber with a reasonable energy requirement under optimal operating conditions. The FBC system resulted in immobilization of 80% of P as triangular or quadrangular pellets, which were verified to be high-purity vivianite crystals by scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDX) and extended X-ray absorption fine structure (EXAFS) spectroscopy. This study provides a pathway for efficient recovery of P as a value-added product (i.e., vivianite) from P-rich wastewaters. Graphical abstract: Image, graphical abstract